The influence of the program code structure on the discretization frequency of the onboard computer of a mobile robot (Моделювання, керування та інформаційні технології, 2019)
The task of code optimization is to refuse third-party libraries that provide a set of features and conditions, which lead to additional load on the microcontroller and reduces its computing capabilities. This task was solved by using only the library for the UART software configuration and the MС work on І2С bus, which allowed to increase the discretization frequency about twice. The error of the algorithmic drift significantly depends on the discretization frequency, at the same time influence of other parameters is almost insignificant, especially when the orders of the integration algorithm are greater than 2